Mapping the Contours: Utopic and Dystopic Perspectives on the Use of AI in Higher Education - Sarkar, Samita; Kumar, Rahul (Canadian Perspectives on Academic Integrity, 2024)
This paper explores the impact of artificial intelligence (AI) on education, with a focus on assessment and academic integrity in higher education. We conducted a thematic analysis of literature on AI and academic integrity, framed by possible utopic and dystopic scenarios. We found that AI can be used to generate text, summarize work, create outlines, and provide information and resources on a particular topic, saving time and money. We argue that effective institutional policies should be established around the use of AI technologies, such as ChatGPT, to better serve the fields of education and academic research. The paper also discusses the implications of AI for university students, including the potential for personalized learning, quick feedback on student work, and improved accessibility for students with disabilities. However, the use of AI in education raises concerns about academic integrity and the potential for cheating. We caution that ethical considerations under existing academic integrity frameworks must be considered when implementing AI in education. The article concludes by calling for further research on the impact of AI on education and the development of guidelines and policies to ensure that AI is used in a responsible and ethical manner.